Promising results from Checkmate 012: better patients or better immunotherapy? - Hunt, Jaime; Velez, Maria A.; Bornazyan, Krikor; Madrigal, John; Carroll, James; Garon, Edward B. (Translational Cancer Research; Vol 6, Supplement 3 (May 26, 2017): Translational Cancer Research, 2017)
Platinum-based doublet chemotherapy has traditionally been the standard of care as initial therapy in patients with advanced (stage IIIB/IV) non-small cell lung cancer (NSCLC). However, now patients with tumors that harbor genomic abnormalities in the epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK), or have high expression of programmed cell death 1 ligand (PD-L1) initially get non-chemotherapy approaches (1-4). Immunotherapy has emerged as a promising, new approach to cancer treatment and the US FDA has approved several immune checkpoint inhibitors (ICIs) in various malignancies. While these ICIs are promising, only inhibitors of the interaction between programmed cell death 1 (PD-1) and its ligand PD-L1 are approved outside of melanoma. Combination therapies are being pursued in an effort to increase the population of patients that may benefit from ICIs.